2022
DOI: 10.3389/fimmu.2022.820046
|View full text |Cite
|
Sign up to set email alerts
|

Update on Tenosynovial Giant Cell Tumor, an Inflammatory Arthritis With Neoplastic Features

Abstract: Rheumatoid arthritis (RA) is a chronic inflammatory disease that leads to joint destruction and bone erosion. Even if many treatments were developed with success in the last decades, some patients fail to respond, and disease chronicity is still a burden. Mechanisms involved in such resistance may include molecular changes in stromal cells. Other explanations can come from observations of tenosynovial giant cell tumor (TGCT), first considered as an inflammatory arthritis, but with unusual neoplastic features. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 81 publications
(145 reference statements)
1
16
0
Order By: Relevance
“…Postoperative radiotherapy was not performed in our patients because the patients did not want it, but it may be a treatment option for postoperative recurrence. The effects of several systemic therapies, including CSF-1 receptor monoclonal antibodies and tyrosine kinase inhibitors, have recently been investigated and are expected to be expanded for future indications [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative radiotherapy was not performed in our patients because the patients did not want it, but it may be a treatment option for postoperative recurrence. The effects of several systemic therapies, including CSF-1 receptor monoclonal antibodies and tyrosine kinase inhibitors, have recently been investigated and are expected to be expanded for future indications [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Described for the first time in 1941, pigmented villonodular synovitis (PVNS), also known as tenosynovial giant cell tumor, is a rare articular disease characterized by an inflammatory synovitis with proliferation of synoviocytes and accumulation of large size monocyte-derived osteoclasts in the synovial tissue of joints 1 . Affecting mostly a single joint, PVNS usually affects young adults with an annual incidence of 1.8 cases out of one million 2 , 3 . The wide spectrum of clinical manifestations includes mainly pain, inflammation and joint swelling leading to a limitation of joint function 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the underlying cause of TGCTs can be targeted by inhibiting signaling between CSF1 and the CSF1 receptor (CSF1R) [ 8 , 9 ]. Research has shown that the monocyte–macrophage lineage marker CD68 stains synovial-lining cells; double staining revealed that CD68 is also expressed by TGCT cells that express CSF1 [ 10 ]. Other work found high CD68 expression levels in several tumor types, particularly TGCTs, compared with normal tissue samples [ 11 ].…”
Section: Introductionmentioning
confidence: 99%